2010
DOI: 10.1095/biolreprod.109.082305
|View full text |Cite
|
Sign up to set email alerts
|

Function-Specific Intracellular Signaling Pathways Downstream of Heparin-Binding EGF-Like Growth Factor Utilized by Human Trophoblasts1

Abstract: Heparin-binding EGF-like growth factor (HBEGF) is expressed by trophoblast cells throughout gestation. First-trimester cytotrophoblast cells are protected from hypoxia-induced apoptosis because of the accumulation of HBEGF through a posttranscriptional autocrine mechanism. Exogenous application of HBEGF is cytoprotective in a hypoxia/reoxygenation (H/R) injury model and initiates trophoblast extravillous differentiation to an invasive phenotype. The downstream signaling pathways induced by HBEGF that mediate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 78 publications
(118 reference statements)
1
41
0
Order By: Relevance
“…The membraneanchored pro-HB-EGF is cleaved by metalloproteinases in order to release the soluble form of HB-EGF [54]. HB-EGF provokes differentiation of trophoblast cells to an invasive phenotype through coordinate activation of PI-3K/Akt, ERK, MAPK14, and JNK pathways [55]. By downregulating HB-EGF in the trophoblast, PIBF might control physiologic trophoblast invasion.…”
Section: Hb-egf Promotes Differentiation Of Trophoblast Cells To An Imentioning
confidence: 99%
“…The membraneanchored pro-HB-EGF is cleaved by metalloproteinases in order to release the soluble form of HB-EGF [54]. HB-EGF provokes differentiation of trophoblast cells to an invasive phenotype through coordinate activation of PI-3K/Akt, ERK, MAPK14, and JNK pathways [55]. By downregulating HB-EGF in the trophoblast, PIBF might control physiologic trophoblast invasion.…”
Section: Hb-egf Promotes Differentiation Of Trophoblast Cells To An Imentioning
confidence: 99%
“…Thus, MAPK8/9 mediates stem cell survival and differentiation responses. MAPK8/9 is activated in mouse and human placental cells in vivo and in vitro and plays a role in adhesion, invasion, survival, and apoptosis (Zhong et al 2004, Cindrova-Davies et al 2007, Kang et al 2007, Lucchi & Moore 2007, Yang et al 2008b, Abell et al 2009, Jessmon et al 2010, Zhu et al 2010. Unlike AMPK, SAPK has no role in mediating loss of potency factors in cultured mouse TSC (Abell et al 2009) or ESC (Xu & Davis 2010).…”
Section: Cellular Stress Signaling Pathwaysmentioning
confidence: 99%
“…However, as only inhibition of the PIK3 pathway had any effect of HBEGFmediated JAR cell, migration we conclude that HBEGFmediated JAR cell migration is mediated by HER1 tyr1068 phosphorylation and sustained downstream activation of the PIK3 and AKT1 signaling pathways. Recently it has also been shown that in HTR8 SVneo and SW.71 trophoblast cell lines, HBEGF-mediated cell migration is mediated by PIK3, MAPK14, ERK, and JNK pathways but with no apparent cross talk between pathways [42]. However, no direct assessment of either MAP2K1 or PIK3 activation was made in this study, and the earliest time point studied was 15 min [42].…”
Section: Discussionmentioning
confidence: 69%